The impact of nationality on the perception of project management and its success among construction project managers in Saudi Arabia - Alabbad, Mohammed; Che Haron, Roziha (Malaysian Institute of Planners (MIP), 2024)
Cultural differences in project teams within the construction industry are a recognized phenomenon in the Kingdom of Saudi Arabia (KSA). This study investigates the crucial role culture plays and how cultural differences among project managers influence their perceptions of two key aspects: project management practices and project success in the context of the Saudi construction industry. A custom questionnaire was used to gather the perceptions of 150 Saudi and non-Saudi project managers from Riyadh city. The statistical tests applied include frequencies, percentages, descriptive statistics, independent t-tests, and univariate analysis of variance (ANOVA). The findings reveal that the nationality of the managers significantly impacts their perceptions of cultural differences, which in turn influences the two aforementioned aspects.